1990
DOI: 10.2307/3899032
|View full text |Cite
|
Sign up to set email alerts
|

Value of Multiple Fecal Indices for Predicting Diet Quality and Intake of Steers

Abstract: The relationship of fecal nitrogen fractions and condensed tannins to dietary crude protein, in vitro organic matter digestibility, and intake of steers was assessed to determine the suitability of these multiple fecal indices for predicting quality of animal diets under free-roaming conditions. Research was conducted on the Texas A&M Native Plant and Animal Conservancy near College Station, located in the Post Oak Savannah region of Texas. Regression equations were used to evaluate relationships between dieta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 32 publications
1
15
1
Order By: Relevance
“…The greatest moisture content occuned simultaneously with the greatest nitrogen content (i.e., during active plant growth as opposed to mature dormant forage). Similar to the inverse relationship between diet quality and fecal DM, fecal OM content will be greater in a relatively lower digestibility ration than in a greater digestibility ration (Huston and Pinchak, 1991) even though prediction of diet quality by means of fecal chemistry indices may be problematic (Leite and Stuth, 1990). Although tick treatment had no direct effect on fecal OM in this cunent study, the general increasing trend observed for fecal OM during the intense tick feeding/blood sampling period would agree with the finding by Tolleson et al (2002) that fecal near-infrared spectroscopy predicted digestible OM in beef heifers fed a pelleted ration was decreased during peak feeding periods of an A. americanum infestation than during nonpeak feeding periods.…”
Section: Dry Matter Organic Matter Volatile Fatty Acids Andphmentioning
confidence: 99%
“…The greatest moisture content occuned simultaneously with the greatest nitrogen content (i.e., during active plant growth as opposed to mature dormant forage). Similar to the inverse relationship between diet quality and fecal DM, fecal OM content will be greater in a relatively lower digestibility ration than in a greater digestibility ration (Huston and Pinchak, 1991) even though prediction of diet quality by means of fecal chemistry indices may be problematic (Leite and Stuth, 1990). Although tick treatment had no direct effect on fecal OM in this cunent study, the general increasing trend observed for fecal OM during the intense tick feeding/blood sampling period would agree with the finding by Tolleson et al (2002) that fecal near-infrared spectroscopy predicted digestible OM in beef heifers fed a pelleted ration was decreased during peak feeding periods of an A. americanum infestation than during nonpeak feeding periods.…”
Section: Dry Matter Organic Matter Volatile Fatty Acids Andphmentioning
confidence: 99%
“…Researchers have used faecal nutrient concentration studies in a variety of indigenous types of wildlife as well as for domestic livestock (Erasmus et al 1978;Belonje & Van den Berg 1980;Holechek et al 1982Holechek et al , 1985Leslie & Starkey 1985;Leite & Stuth 1990;Irwin et al 1993;Grant et al 1995Grant et al , 1996Grant et al , 2000MacLeod et al 1996;Vorster 1996;Wrench et al 1996Wrench et al , 1997Van der Waal et al 2003;Codron et al 2005;Botha & Stock 2005;Mbatha & Ward 2006). Leslie & Starkey (1985) found that faecal nitrogen concentration increases with an increase of the nitrogen concentration of the herbivore's diet.…”
Section: Introductionmentioning
confidence: 99%
“…Leslie & Starkey (1985) found that faecal nitrogen concentration increases with an increase of the nitrogen concentration of the herbivore's diet. Total faecal nitrogen is reported to correlate with the soluble nitrogen fraction in faeces (Leite & Stuth 1990) although the ratio of insoluble nitrogen in faeces increases as the forage quality decreases (Leite & Stuth 1990). The faecal nitrogen concentration of herbivores is considered to be a reliable predictor of pasture digestibility, provided that the diet consists primarily of grasses which have similar chemical properties, but it is less effective when the diet consists primarily of browse (Holecheck et al 1982;Wofford et al 1985;Grant et al 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Chemical composition of faeces as an index of dietary quality has been examined quite extensively (Moir I 960a, 1960b;Erasmus et al 1978;Holechek et al 1982: Leslie & Starkey 1985Leite & Stuth 1990: Wrench et a/. 1997.…”
Section: Introductionmentioning
confidence: 99%